Analysis of Student Motivation of English Learning as a Second Language - Zulfa, Vania; Zahidah, Assyifa Nur (PT. BATARI EDU CALYA, 2023)
This research aimed at investigating the students’ motivation in English learning as a second language. Motivation is considered as a key feature in the success of language learning and has great effect on the efficiency and productivity of English language teaching.Students’ English learning orientation from the perspective of various important motivation concepts (from Gardner’s integrativeness/instrumentality to motivational self-system) and the notion of English as an international language. According to Rost (2006) motivation has been called the “neglected heart” of language teaching. Without student motivation, there is no pulse; there is no life in the class. The issue of motivation, particularly in EFL settings, is so important that other considerations about teaching methodology seem to pale in comparison. It is important to think about motivation as the essence of language teaching because of the stark realities of learning English for most of our students.